Exploring Students’ Learning Experiences Under the China–Korea Cooperative Teaching Model: A Positive Psychology Perspective - Lei Song; Zhenzhen Huang; Luhao Cao; Shanshan Yang (Behavioral Sciences)
Based on the theory of learning experiences and the Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment (PERMA) model, this research aims to interpret the learning experiences of students majoring in Animation under the China–Korea cooperative teaching model from a perspective of positive psychology. Purposive sampling was conducted to carry out semi-structured interviews with 25 students and 3 teachers. In the thematic analysis, it was found that students’ learning experiences are accompanied by emotions, both positive and negative, and that emotions are correlated with engagement, relationships, meaning, and achievement, which together constitute students’ learning experiences. In addition, this research confirms that students’ learning motivation and learning experiences mutually affect each other, with learning motivation affecting students’ learning experiences on the one hand, and positive elements of learning experiences enhancing students’ learning motivation and bringing positive learning outcomes on the other.